2020
DOI: 10.1177/2048872620923641
|View full text |Cite
|
Sign up to set email alerts
|

Pentraxin 3 in primary percutaneous coronary intervention for ST elevation myocardial infarction is associated with early irreversible myocardial damage

Abstract: Background The inflammatory marker long pentraxin 3 (PTX3) has been shown to be a strong predictor of 30-day and one-year mortality after acute myocardial infarction. The aim of this study was to evaluate the kinetic profile of PTX3 and its relationship with interleukin 6 (IL-6), high-sensitive C-reactive protein (hs-CRP) and infarct size. Methods PTX3, IL-6 and hs-CRP were measured at predefined time points, at baseline (before percutaneous coronary intervention (PCI)), at 12 and 72 hours after PCI in 161 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Today, CRP is a well-established biomarker associated with inflammation in cardiovascular disease. In accordance with previous findings [ 26 , 27 , 28 ], we observed that PTX3 had faster kinetics than CRP, with high values found already in the acute samples. In contrast to CRP, PTX3 is produced locally at the site of tissue trauma and inflammation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Today, CRP is a well-established biomarker associated with inflammation in cardiovascular disease. In accordance with previous findings [ 26 , 27 , 28 ], we observed that PTX3 had faster kinetics than CRP, with high values found already in the acute samples. In contrast to CRP, PTX3 is produced locally at the site of tissue trauma and inflammation.…”
Section: Discussionsupporting
confidence: 93%
“…However, as PTX3 was normalized 3 months after the PCI, it seems that the intervention helped to reverse the process leading to increased levels in the acute samples. There are previous studies that report increased levels of PTX3 in acute samples [ 27 , 28 ]. Others report increased PTX3 after PCI [ 9 , 30 , 31 ], and some report a reduction 1–3 days after PCI [ 9 , 27 ], but we have analyzed all three time points, which enables direct comparisons of the differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result may be correlated with a higher median pentraxin-3 level in STEMI than in NSTEMI patients ( 31 ). Pentraxin-3 level was significantly correlated with infarct size ( 32 ) and thrombus burden ( 28 ). When we grouped the studies by the length of follow-up, the value of pentraxin-3 in predicting cardiac events was evident in studies with short-term follow-up than those with relatively long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…8 Butt et al. 9 investigated the kinetic of PTX3 as well as its correlation with inflammatory biomarkers and infarct size in 161 patients undergoing pPCI from the MITOCARE trial. PTX3 showed a steep increase in the early phase of STEMI (first 12 hours after admission) followed by a gradual decrease from 12 to 72 hours, therefore mimicking interleukin-6 and cardiac markers of necrosis, at variance from high-sensitive C-reactive protein (which continuously increased after 72 hours).…”
Section: Pentraxin 3 As a Novel Marker Of Myocardial Reperfusion Injurymentioning
confidence: 99%